The impact of brand equity on employee's opportunistic behavior: A case study on enterprises in Vietnam - Tran Quang Bach; Le Quoc Hoi; Nguyen Hoai Nam; Dieu Linh Tran; Nguyen Thi Thuy Quynh; Thi Thanh Thuy Tran (Journal of Risk and Financial Management, 2021)
Brand is considered a valuable asset that a business wants to create and maintain growth throughout its business cycle. This paper examines the impact of corporate brand equity on employees' opportunistic behavior. The paper uses quantitative research methods, through linear SEM (Structural Equation Modelling) analysis of structural model with a scale of 609 samples of employees of enterprises in Vietnam. The research results show that corporate brand equity has a negative impact on employees' opportunistic behavior. In the relationship between these two factors, trust and emotional engagement act as intermediate factors. Additionally, the research demonstrates that trust has a positive effect on all three components of employee engagement, including emotional engagement, computational engagement, and standards-based engagement. On that basis, the research suggests a number of recommendations to minimize the opportunistic behavior of employees in the enterprise. The findings of this study have shown the importance and impact of brand equity on employee opportunistic behavior. These are meaningful contributions in both theory and practice to help businesses gain deeper insight into brand equity and the need to pay attention to building and developing durable brand equity for businesses. At the same time, it is an important basis for the next research projects.
Keywords: 330; computational engagement; corporate brand equity; emotional engagement; opportunistic behavior; standards-based engagement; trust